Survey on Integrated Design of Smartphone Interface with Multiple Image Processing Methods (International Journal of Engineering and Computer Science, 2017)
The direct light from the projector is harmful to the speaker’s face when facing digital projector. So the digital projector with smartphone is used to reduce the shining light from projector and thus protect the speaker’s face. First, the smart phones capture the speaker’s location including projector screen. After captured the image it undergoes preprocessing methods are face detection, back-ground differencing, skin color recognizing method and ROI. After the preprocessing the location of the speaker's face is detected and the smart phone super imposed the black mask over the speaker's face [1].